Plant gene regulatory network system under abiotic stress - Hong-bo, Shao (Acta Biologica Szegediensis, 2006)
Plants differ from animals in many aspects, but the important may be that plants are more easily influenced by environment than animals. Plants have a series of fine mechanisms for responding to environmental changes, which has been established during their long-period evolution and artificial domestication. These mechanisms are involved in many aspects of anatomy, physiology, biochemistry, genetics, development, evolution and molecular biology, in which the adaptive machinery related to molecular biology is the most important. The elucidation of it will extremely and purposefully promote the sustainable utilization of plant resources and make the best use of its current potential under different scales. This molecular mechanism at least include environmental signal recognition (input), signal transduction (cascades of biochemical reactions are involved in this process), signal output, signal responses and phenotype realization, which is a multi-dimensional network system and contain many levels of gene expression and regulation. We will focus on the molecular adaptive machinery of plants under abiotic stresses and draw a possible blueprint for it. Meanwhile, the issues and perspectives are also discussed.